Mesenchymal Stem Cells Induce Regulatory T-cell Population in Human SLE (Bangladesh Journal of Medical Science, 2020)
Background: The mechanisms underlying peripheral disorders during systemic lupus erythematosus (SLE) were found to be shared with tolerance disorders and mediated by T-regulator (T-reg) cells. Mesenchymal stem cells (MSCs) may inhibit T-cell subset differentiation and induce the T-reg cell phenotype. However, the capacity of MSCs to promote functional T-reg cells in SLE patients remains unclear.Objectives: This study aimed to analyze the capacity of MSCs to induce the production of functional CD4+ CD25+ Foxp3+ T-reg cells, in vitro, under co-culture conditions with human SLE cells.Methods: This study used a pre- and post-test control group design. Peripheral blood mononuclear cells (PBMCs) were extracted from SLE patients at the Kariadi Hospital, and MSCs were derived from human umbilical cords (hUCs) The PBMC control group was treated with standard medium, and the treatment group was co-cultured with hUC-MSCs. After 24 hours of co-culture incubation, T-reg cells were removed from the PBMC pool, using magnetic-activated cell sorting (MACS), and the population was assessed using the trypan blue exclusion assay.Results: A significant increase in the population of T-reg cells was observed (P < 0.001) after 24 hours of co-culture incubation with hUC-MSCs.Conclusion: This study concluded that MSCs have the capacity to enhance the T-reg population in human SLE PBMCs.Bangladesh Journal of Medical Science Vol.19(4) 2020 p.743-748